Anthraquinones from Hedyotis pinifolia - Duy, Le Hoang; Phi Phung, Nguyen Kim (Vietnam Journal of Chemistry, 2014)
Hedyotis pinifolia Wall ex G.Don (Vietnamsese name An điền l¸ th«ng), family of Rubiaceae, has not yet been chemically studied. From the aerial parts of H. pinifolia, four anthraquinones had been isolated: 1,6-dihydroxy-7-methoxy-2-methylanthraquinone (1), 1,6-dihydroxy-2-methylanthraquinone (2), 3,6-dihydroxy-2-methylanthraquinon (3) and 1,3,6-trihydroxy-2-methylanthraquinone (4). Their chemical structures were established by spectroscopic analysis.   Keywords: Rubiaceae, Hedyotis pinifolia, anthraquinone.